Implementasi Medical Check- Up (MCU) Untuk Lansia Pada Program Kkn Bhanu Braja Di Desa Mekarsari - Adinda Aulia; Sherliane Vanesa; Pasha Shabrina; Al Fadhli; Rizky Ramadhan Tri Oktarian (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Community Service Program (KKN) serves as a platform for students to apply academic knowledge in improving community welfare and public health. One of the initiatives conducted by the Bhanu Braja KKN group in Mekarsari Village was a Medical Check-Up (MCU) program for the elderly to facilitate early detection of non-communicable diseases. This activity aimed to raise awareness among the elderly about the importance of regular health examinations and healthy lifestyles. The MCU was carried out for 40 elderly participants at Posyandu Merpati 4, including examinations of blood pressure, blood glucose, cholesterol, and uric acid levels. The results showed that most participants were within normal ranges, although several cases of hyperglycemia and hyperuricemia required further medical attention. The program effectively increased health awareness among the elderly and encouraged local health cadres to continue routine check-up activities. This initiative is expected to promote a culture of regular health monitoring and healthy living among rural communities.